Legal nature of public-private partnership in the field of construction and operation of transport roads in Ukraine - Mentukh Nataliіa (Actual problems of law (Aktual’ni problemi pravoznavstva), 2024)
The article is devoted to the study of the legal nature of public-private partnership in the field of construction and operation of transport routes in Ukraine based on the analysis of theoretical foundations. It is argued that ensuring sustainable development, improving the investment climate, increasing the competitiveness of the national economy, creating conditions for Ukraine’s transition to an innovative path of development, and stimulating the process of regional development largely depends on the availability and quality of infrastructure. It is substantiated that public-private partnership is one of the effective ways to develop and support the field of construction and operation of transport routes. Attention was drawn to the need for the construction of transport infrastructure within the framework of the application of the public-private partnership system. At the same time, it was noted that the successful implementation of the public-private partnership model will allow to develop the country’s infrastructure at the expense of saving budget funds, increase the efficiency of design, strengthen the responsibility of state officials for the distribution of risks and increase the inflow of domestic and foreign investments. The author states that the mechanism of public-private partnership can be effectively used in Ukraine to restore destroyed objects of transport infrastructure, rebuild the destroyed infrastructure and its further maintenance. Scientific positions on the development of public-private partnership mechanisms in the field of transport infrastructure are considered. Proposals for improving the theoretical foundations of the specified problem have been formulated.